Dirty Vote Film: Unruly Politics Movement In Digital Space - Ferdiansah, Farabi (Jurnal Studi Jurnalistik, 2024)
Dirty Vote: Unruly Politics Movement in Digital Space analyzes the impact of the documentary film ‘Dirty Vote’ which released during Indonesia's pre-election quiet period. This documentary exposes alleged election fraud and abuses of power under President Joko Widodo's leaders. Dirty Vote represents a form of unruly politics, challenging formal political structures and fostering public discourse on political transparency. The term “unruly politics” is used to describe political engagement that operates outside conventional norms and institutions. In this case, Dirty Vote symbolizes a non-traditional, confrontational form of political discourse that utilizes digital media to bypass official restrictions.Through digital platforms, Dirty Vote has significant attention, underscoring the role of social media in amplifying marginalized voices and circumventing governmental restrictions. This analysis situates the film within broader discussions of digital activism, demonstrating how digital spaces enable citizens to address systemic political issues and advocate for democratic integrity.